PRODUCTION OF URANIUM-MOLYBDENUM ALLOY AS A CANDIDATE FOR NUCLEAR RESEARCH REACTOR FUEL - Suryaman, Ganisa Kurniati; Wildan, Muhammad Waziz; Supardjo, Supardjo; Agus Susanto, Yatno Dwi (Urania : Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2018)
PRODUCTION OF URANIUM−MOLYBDENUM ALLOY AS A CANDIDATE FOR NUCLEAR RESEARCH REACTOR FUEL. Research and development on high density uranium for nuclear research reactor fuel is still in progress. Uranium-molybdenum alloy is one of the strongest candidates of nuclear research reactor fuel material. The properties and characteristics of U-Mo alloy is of important consideration for the selction of the fabrication techniques for the production of  the fuel. In this work, uranium-molybdenum (U-Mo) alloys with varied molybdenum content have been produced succesfully by arc melting technique. The molybdenum content variations were 7 %wt, 8 %wt, 9 %wt and 10 %wt Mo. The melting process was done 5 times to achieve homogenization. Metallographic micrograph shows the presence of dendritic structure. XRD examination result affirms the presence of 2 phases of γ-U phase and d-U2Mo phase. Microhardness Vickers test shows higher hardness value for Uranium-molybdenum alloy with higher molybdenum content.Keywords: U−Mo alloy, research reactor, fuel.